Interest rate risk of life insurers: Evidence from accounting data - Axel Möhlmann (Financial Management, 2021)
Life insurers are exposed to interest rate risk as their liability side is typically more sensitive to interest rate changes than their asset side. This paper explores why insurers assume this risk using a new accounting-based method to measure the interest rate sensitivity of assets and liabilities. Calculation at the insurer level yields a wide duration gap with pronounced heterogeneity in the cross-section. This could be explained by alternative investment strategies, such as asset insulation, which are at odds with interest rate risk management. Using a 2014–2018 panel, factors associated with interest rate risk support this view.
Keywords: 650; asset liability management; duration gap; insurance investment management; interest rate risk; life insurers; E43; G11; G22